Municipal Young Assembly - Paixão, H.; Romeiro, S. (Open Schools Journal for Open Science, 2020)
This project results from the need to encourage young people to actively participate in the life of the Municipality. In the 2018/2019 academic year, the theme “Climate change: reversing global warming” was worked on in almost all curricular areas, in two 8th grade classes of the school. The classes elected their own "Young Municipal Deputies". Throughout the project, students were prepared for the final session, where each school represented a party and all parties presented and defended their proposals, to all the Assembly.